Nilai Karakter Kemandirian Dalam Kumpulan Dongeng Si Kancil sebagai Penguatan Materi Bahasa Indonesia di Sekolah Dasar - Sugiyanto, Agus; Widayati, Mukti; Pratiwi, Veronika Unun (Cetta: Jurnal Ilmu Pendidikan, 2025)
The lack of effective local culture-based learning media is a challenge in instilling the value of independence in character education in elementary schools. This study aims to (1) describe the character value of independence in the Collection of Fairy Tales of Si Kancil and (2) describe the strengthening of the character value of independence as part of the teaching material for Indonesian language content in elementary schools. This research uses descriptive qualitative method with literary sociology approach and dialectical technique. The main data in the form of expressions that reflect the value of independence are taken purposively from five stories in the Collection of Fairy Tales of Si Kancil by M.B. Rahimsyah A.R. published by Lingkar Media in 2013. Secondary data were obtained from academic literature related to character, literary sociology, and children's literature. Data collection was conducted through literature study, analytical reading, and note-taking, with Miles & Huberman model analysis and validation through triangulation of methods and sources. The results showed that the Collection of Fairy Tales of Si Kancil contains four aspects of independence: emotional, economic, intellectual, and social. These values can be strengthened in Indonesian language learning through interactive strategies, such as group discussion, dramatization, story rewriting, as well as written reflection and case study. This study concludes that the collection of Fairy Tales of Si Kancil contains values of independence including emotional, economic, intellectual, and social aspects, which are relevant for strengthening students' character and can be effectively integrated in Indonesian language learning through interactive strategies in elementary schools.